Management of Islamic Boarding School Caretakers in Improving the Economic Independence of Students Through Agribusiness Entrepreneurship at the At-Tadzkir Islamic Boarding School in Majalengka - Nur Alim, Mohamad; Mohammad Maulana Nur Kholis (Papanda Publisher, 2025)
This study analyzes the role of boarding school management in improving the economic independence of students through an agribusiness entrepreneurship program at the At-Tadzkir Islamic Boarding School in Majalengka. Using a qualitative approach with a case study method, data was collected through in-depth interviews with the boarding school leader (K.H. Didin Misbahuddin), students, and teachers, as well as observation and documentation. The findings show that the management applies structured and organized management strategies (Planning, Organizing, Actuating, Controlling) to integrate agribusiness entrepreneurship into the boarding school curriculum. This implementation not only equips students with practical business skills but also fosters independence, confidence, and responsibility. This study emphasizes that a holistic and collaborative managerial approach by pesantren caregivers can be an effective model for empowering students economically.